Maintenance of the Gold Value of the Fund's Assets. (Pamphlet Series, 1971)
This paper discusses Article IV, Section 8 of the Articles of Agreement which states the requirement of maintenance of the gold value of the IMF's assets. Each member of the IMF is bound to maintain the gold value of the IMF's holdings of the member's currency notwithstanding changes in the par or foreign exchange value of the currency. This obligation applies to devaluation, depreciation, revaluation, and appreciation. It prevents the IMF from making profits or sustaining losses as a result of changes in the value of its currency holdings. An additional purpose is to enable the IMF to continue to conduct its operations in a manner consistent with its purposes, notwithstanding such changes.